Disfuncionalidad familiar y el desarrollo de psicosocial en los adolescentes de la Unidad Educativa San Camilo año 2019 - Chacon Arana, Iduar Aníbal (2019)
The following investigation has the title of "Family dysfunctionality and the development of psychosocial in the adolescents of the educational unit" San Camilo "year 2019", since the population of this educational unit presents characteristics that motivate the generation of this research, the objectives of the research are to determine, identify, analyze the influence of family dysfunction in the psychosocial development of the adolescents of that educational unit, as well as to suggest a program of participative integration between parents and students to improve the current problem. The methodology used in the research is quantitative, since it responds to a numerical and generalizable analysis of the phenomenon to be studied, the population was parents, teachers and students of the educational unit, the sample of this population was 150 people , which was divided into 20 teachers, 65 parents, 65 students, thus reaching the total sample to which the surveys would be applied. The survey was formed by 8 questions that responded to interests and were based on the theory of research. The most important conclusion was that I affirm that if there is influence of family dysfunction in the psychosocial development of adolescents of the Educational Unit "San Camilo" since it responded to the hypothesis, for the practical proposal workshops based on "Family cohabitation" were generated "With three important themes related to the results and the theory of research which is based on family dysfunction and psychosocial development.